The Effect of The Communicative Language Teaching Through English Oral Presentation Toward Midwifery Students’ Speaking Skill at Medika Suherman University (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Nowadays, midwifery and medical work adopted many concepts, descriptions, and terminologies in English. As the demand of the curriculum in midwifery major, English took the magnificence role in facilitating students, preparation for professional requirements, trainings, and research. That was why English became the crucial part for midwifery students to research and practice their English in the real working field. The purpose of the research was to know that this research was expected to confirm and clarify the exposure and practice of Communicative Language Teaching (CLT) through English oral presentation language testing gave the better solution to enhance the speaking skill of midwifery students at Medika Suherman University. The research applied the quantitative analysist that covered descriptive analysis statistic and the t – test. In order to achieve the objective of the research which was used the pre-test and the post-test as the tool to measure the speaking skill ability. The population of the research was 50 students midwife of the second semester at Medika Suherman University, Cikarang Bekasi. The sample of the population was 30 students midwife wahich was selected by purposive random technique. There were four meetings of learning and researching process during the experiment. Before the experiment was conducted, the students were given a pre-test. At the end of the experiment, the students did the post-test. The result of the research proved that the post-test scores were better that the pre-test score. The research concluded that the output of the paired test sample with the Sig. (2-tailed) score was 0.000 < 0.05. It stated that the H0 was rejected, and Ha was accepted. Moreover, it showed that there was an effect of the English oral presentation toward midwifery students’ speaking skill at Medika Suherman University. According to the result, after the exposure and practice of Communicative Language Teaching (CLT) through the English oral presentation language testing, in fact, it was the one of the effective approaches to improve the students midwife speaking skill ability and enthusiasm in learning English at Medika Suherman University.